Impact of Personnel Control on Organizational Performance of Elected Government Agencies in Kailali District - Mahara, Mahendra Singh (KMC Journal, 2026)
This study examines how personnel control influences the organizational performance of the elective government agencies in the Kailali District in Nepal and the mediating effect of employee motivation is tested. Primary data were gathered using a structured questionnaire in 216 employees in 13 elected local governments using a quantitative, cross-sectional explanatory research design. Personnel control was the multidimensional concept which included recruitment and training, monitoring and organizational culture, employee retention and promotion and workplace policies and socialization. Data analysis was performed based on descriptive statistics, correlation, multiple regression, and formal mediation analysis based on Hayes PROCESS macro (Model 4) using 5,000 bootstraps. The findings indicate personnel control to be a significant and positive factor in the performance of an organization. There are high positive influences in recruitment and training, monitoring and organizational culture, and employee retention and promotion show a relatively weak impact. Employee motivation is also greatly increased through personnel control and this leads to an improvement in organizational performance. The mediation analysis proves that employee motivation partially mediates the relationship between personnel control and organizational performance. The results can be viewed as providing an empirical evidence based on a Nepalese context of the public-service and can provide an implication on how to improve personnel control systems to enhance motivation and performance in an elected government agency.